VAGINAL ELECTRICAL RESISTANCE DURING DIFFERENT PHASE OF ESTRUS CYCLE IN COWS AND HEIFERS - PATIL, S R; PAWSHE, C H (The Indian Journal of Animal Reproduction, 2011)
The present research study was conducted for detection of estrus and changes of vaginal resistance during different phase of estrus cycle and pregnancy with the help of electronic probe ’DRAMINSKI’ heat detector in cows and heifer after the treatment of PGF 2., • The result revealed that in cows the mean vaginal electric resistance (VER) was significantly low (230 W) during estrus, than proestrus (295 W), metestrus (262 W) and diestrus/ pregnancy ( 260 W) ( P < 0.01). Also in heifers, the mean VER was significantly low (222.5 W) in estrus than proestrus (261.25 W), meteslrus (274.5 W) and diestrus/ pregnancy (264.62 W) (P < 0.01). There ls no significant differences between cows and heifers in VER of different phases of estrus cycle and pregnancy period.